Research on the static performance of a gas thrust bearing for the eddy current brake helium turbo-expander. (April 2019) - Li, S S; Fu, B; Zhang, Q Y
Abstract: As an important refrigeration component, the turbo-expander affects the continuous operation of the helium refrigerator. In order to improve the reliability of the refrigerator, a helium turbo-expander with the eddy current brake was designed by Institute of Plasma Physics Chinese Academy of Sciences. The axial support is the critical technology to ensure the stability of the bearing-rotor system for the turbo-expander. This study is based on the static gas thrust bearing of the home-made turbine, the performance of the bearing was investigated by computational fluid dynamics simulation. The findings in this paper can provide an important guideline for the optimal design of the thrust gas bearing.